Vinho: uma imagem arquétipa - Amui, Juliano Maluf (2007)
This study approaches the symbolism of wine from its archetypal foundations, searching to understand its purpose and meanings to the subjective psyche. The work begins with the explanation of the concept of psyche on the analytical psychology s point of view, as well as the notion of psychic image in its personal and archetypal aspect, aiming at clarifying the idea of archetypal image. After that, using the constructive-synthetic or amplification method, developed by Carl Gustav Jung, the wine is tackled while image, based on the history of the civilizations. The following archetypal lines: wine and nature x culture, wine and sexuality, wine and drunkenness, wine and spirit and wine and transformation, are considered in elapsing of the work, allowing the dialogue between the archetypal inherent in the image of wine and its psychological phenomenology, that is, the purpose of its advent, as well as its meanings while images of dreams and fantasies. The contents amplified by the synthetic-constructive method of Jung are analyzed in accordance with central concepts of the analytical psychology. Finally, the author discusses the information raised, clarifying and punctuating the aspects of wine that characterize it as an archetypal image